Anti-thrombin is expressed in the benign prostatic epithelium and in prostate cancer and is capable of forming complexes with prostate-specific antigen and human glandular kallikrein 2. - Cao, Y; Lundwall, A; Gadaleanu, V; Lilja, H; Bjartell, A (2002)
Anti-thrombin, a member of the serpin family and an inhibitor of thrombin and blood coagulation factor Xa, was recently shown to inhibit angiogenesis and tumor growth. In the present study, we examined the expression of anti-thrombin in benign and malignant prostate gland. Using immunohistochemistry, anti-thrombin was found in prostate epithelium and stroma cells. Tissue microarrays of tumors (n = 112) and three different prostate cancer cell lines (PC-3, LNCaP, and DU-145) were all positive for anti-thrombin. Abundant expression in a population of prostatic tumor cells was further evidenced by in situ hybridization experiments. The immunostaining for anti-thrombin was confined to the cytoplasm, was most intense in Gleason grade 3 tumors, and in part overlapped with that of prostate-specific antigen. Western blotting of benign and malignant tissue homogenates revealed a predominant 58-kd anti-thrombin immunoreactive component. In vitro, anti-thrombin formed complexes more readily with human kallikrein 2, particularly in the presence of heparin, and less efficiently with prostate-specific antigen. Both complexes could be recognized by polyclonal and monoclonal IgGs against anti-thrombin. We conclude that anti-thrombin is widely expressed in prostate cancer but is gradually lost in tumors of high Gleason grade. Anti-thrombin may act as a local anti-angiogenic factor, the effect of which is partially lost in poorly differentiated prostatic tumors.